On the Myth of Disenchantment - McCutcheon, Russell T. (Harvard theological review, 2018)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0017816018000299/resource/name/firstPage-S0017816018000299a.jpg